Ethical work climate and firm performance. - Khademfar, Mohammad; Idris, Khairuddin; Omar, Zoharah; Ismail, Ismi Arif; Arabamiry, Seddigheh (Center for Promoting Ideas (CPI), USA, 2013)
This study aimed to investigate the relationship between Ethical Work Climate (EWC) and Firm Performance. The research conducted within Malaysian manufacturing companies. Since the unit of analysis was organization, 200 cases were selected randomly. The result of pilot test confirmed that all instruments are reliable to be used. Data was collected using a self-administered questionnaire. Managers as target respondent explained their perception via standardized questionnaires. Previous studies show that there is not enough documented research on such topics in Malaysia. So, it may open a new phase and develop the body of knowledge in this area. Based on the results, the study found a high correlation and significant relationship between EWC and Organizational Performance (OP) in Malaysian firms. It means the perception of managers regarding the ethical manners and ethical climate is positive.